Microstructural characterization and bond strength of the interface area between dental core and body porcelains - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2004)
To fabricate all-ceramic fixed partial dentures with appropriate fracture strength and aesthetics, new ceramic core materials were recently introduced into the dental market. In this study, the bond strengths of the core and body porcelains of 3 different brands were determined by 4-point bending tests. Two of these brands were hot-pressed ceramics and one was glass-infiltrated presintered alumina. There were significant statistical differences in the bond strength values of the specimens of the three groups, the highest values belong to the combination of the glass-infiltrated presintered alumina as core and feldsphatic porcelain as body porcelain. Scanning Electron Microscopy investigations were carried out to examine the fracture surfaces.
Keywords: core porcelain; body porcelain; bond strength